Exploring the Impact of Digital Platforms on Teaching Practices: Insights into Competence Development and Openness to Active Methodologies - Víctor Díaz-Suárez; Miriam Martín-Paciente; Carlos M. Travieso-González (Applied System Innovation)
This research examines the impact of digital transformation on teaching practices and evaluates educators’ training requirements within the European Framework for the Digital Competence of Educators (DigCompEdu), focusing specifically on its implementation in the Canary Islands’ educational system. Through a quantitative study involving 546 teachers from primary and secondary institutions during the 2023/2024 academic year (confidence level: 95%, margin of error: 4.15%), we analyzed the relationship between digital competence development and educational innovation. Results indicate significant gaps in four key areas: digital content creation, innovative teaching methodologies, assessment strategies, and feedback mechanisms. The findings reveal a direct correlation between insufficient educational funding and limited professional development opportunities in digital competencies. This study identifies critical areas requiring immediate attention, including increased budgetary allocation for technological infrastructure, systematic professional development programs aligned with DigCompEdu standards, and the restructuring of current innovation approaches in educational institutions. This research contributes to the understanding of how educational systems can effectively adapt to digital transformation while highlighting the crucial role of both financial investment and structured training programs in fostering successful educational innovation, ultimately emphasizing that adapting education systems to digital realities is essential for ensuring future success in an increasingly digitalized educational landscape.